A review of atomic layer deposition for high lithium-ion battery performance - Edy Riyanto (Elsevier, 2021)
The technology development of electrochemical energy storage devices including lithium-ion battery is urgently needed to support the increased demand for renewable energy and production growth of portable electronic devices. Extensive research on nanostructural engineering aims to improve battery performance in terms of capacity, energy density, cycling ability, and Coulombic efficiency. This review describes the concept of atomic layer deposition (ALD) and focuses on ALD for Li-ion battery. Within the last few years, interest in the nanostructured materials synthesized by ALD to enhance battery performance has rapidly improved. Given the urgent requirement for reliable materials for high battery performance, ALD is a robust method for developing and fabricating nanostructure materials for next-generation Li-ion batteries, especially in the design of anode and cathode electrodes of the batteries.